Building capacity to tackle the threat of antimicrobial resistance in aquaculture in Asia and Africa using a One Health approach - Verner-Jeffreys, David (WorldFish, 2024)
The presentation highlights the challenges of antimicrobial resistance (AMR) in aquaculture across Asia and Africa and advocates for a One Health approach to address this issue. It outlines the use of antibiotics in aquaculture, the emergence of resistant bacterial strains, and the role of conjugative plasmids in spreading AMR. Proposed solutions include capacity building through regulation enhancement, AMU/AMR surveillance, laboratory diagnostics, and biosecurity measures. The presentation emphasizes global collaboration, exemplified by the UK FAO Reference Centre for AMR and initiatives like training, AMU surveys, and pilot programs. It underscores the importance of cost-effective disease control strategies, including vaccination and alternative measures, to promote sustainable aquaculture practices.